Validation of the Computerized Pediatric Triage Tool, pediaTRI, in the Pediatric Emergency Department of Lenval Children's Hospital in Nice: A Cross-Sectional Observational Study - Tran, Antoine; Valo, Petri; Rouvier, Camille; Dos Ramos, Emmanuel; Freyssinet, Emma; Baranton, Emma; Haas, Olivier; Haas, Hervé; Pradier, Christian; Gentile, Stéphanie (Frontiers in Pediatrics, 2022)
Introduction A reliable pediatric triage tool is essential for nurses working in pediatric emergency departments to quickly identify children requiring priority care (high-level emergencies) and those who can wait (low-level emergencies). In the absence of a gold standard in France, the objective of our study was to validate our 5-level pediatric triage tool –pediaTRI– against the reference tool: the Pediatric Early Warning Score (PEWS) Materials and methods We prospectively included 53,664 children who visited the Pediatric Emergency Department at Lenval Children’s Hospital in Nice in 2017. The performance of pediaTRI to identify high-level emergencies (gravity levels 1 and 2) was evaluated in comparison with a PEWS ≥ 4/9. Results pediaTRI agreed with the PEWS for 45,099 of the patients (84%): 15.9% (15.6-16.2) of the patients were over-triaged and 0.1% (0.1-0.1) under-triaged compared with the PEWS. pediaTRI had a sensitivity of 71.9% (69.3-74.3), a specificity of 84.3% (84.0-84.6%), and positive and negative likelihood ratios of 4.6 (4.4-4.8) and 0.3 (0.3-0.4), respectively, for the identification of high-level emergencies. However, the likelihood ratios were lower for those presenting with a medical complaint (3.7 (3.6–3.8) v 9.3 (5.3–16.5) for trauma), and for younger children (1.1 (1.0–1.1) from 0 to 28 days, and 1.6 (1.3–1.8) from 28 days to 3 months). Conclusion pediaTRI has a moderate to good validity to triage children in a Pediatric Emergency Department with a tendency to over-triage compared to the PEWS. Its validity is lower for younger children and for children consulting for medical complaint.